Assessment and cultural ecosystem service mapping in mountain protected areas – “Pirin” National park - Maria Glushkova; Miglena Zhiyanski; Rositsa Yaneva (Silva Balcanica, 2023)
The assessment and mapping of ecosystems and their services is considered an important action that effectively contributes to proper understanding of how ecosystems support human well-being, and furthermore – to promote the sustainable use of natural resources. The diversity of cultural landscapes, especially in mountain areas, is a significant prerequisite for a variety of cultural ecosystem services that are valuable for the society. This evaluation is the basis for environmental management practices and policymaking. The study presents an approach for assessment and mapping of cultural ecosystem service (CES) “Cultural heritage” that is recognised as important and is provided by mountain protected areas (PAs) in “Pirin” National Park. The data from the Management Plan of “Pirin” NP were used for characterization and biophysical assessment of the condition of forest ecosystems and their potential to provide CESs. The analysis of the results revealed that the conservation regime allowed the territories to preserve a high degree of naturalness and a very good ecological condition as 94.80% of forest ecosystems are assessed with score 4 –“good” condition and 0.44% are with “very good” condition – score 5. The majority of forest ecosystems with “very good” ecological condition are Pinus peuce forests, located mainly on the territory of the reserves “Bayuvi Dupki- Dzhindzhiritsa” and “Yulen”, proving the importance of the protective regime of the territories. Forest ecosystems with average and high capacity to provide ES "Cultural heritage" prevailed, which is consistent with well-preserved and unique nature, the diversity of landscapes, and species richness. Considerable areas were assessed with score 5 – very high capacity, mostly on the territory of the reserves “Bayuvi Dupki- Dzhindzhiritsa” and “Yulen”, and at the foothill of the huts.